Implementasi dan Analisis Digital Marketing pada Toko Kebutuhan Bayi dan Anak - Theresia Antonia Widiastuti; Yenni M Djajalaksana (Maranatha University Press, 2022)
The use of digital marketing to market products in this modern era has flourished due to the COVID-19 Pandemic emergence. The interactive ability possessed by digital marketing in providing 2-way communication in real time is one of the attractive advantages for business owners. Toko Makmur is a brick-and-clicks store that sells various needs for babies and children. Toko Makmur chose digital marketing as a marketing medium to market its products to the target market. Digital marketing at Toko Makmur was done by optimizing the use of Facebook and Instagram social media, optimizing the use of Google My Business, and creating a blog site called “Gagasan Bunda” for soft marketing using Wordpress. Optimization is carried out both organically by optimizing SEO (Search Engine Optimization) and uploading information content about mothers and children. In addition, Toko Makmur also conducted paid advertisement through social media Facebook. The data sources used to see the results of digital marketing implementation were from Google Analytics, Instagram Insight, Facebook Insight, and Google My Business Insight.